Desplazamientos y procesos de identificación en las experiencias interculturales de vida de niños indígenas y migrantes en Argentina - Padawer, Ana (2015)
In this paper we analyse migrants and indigenous ‘children identification processes in Argentina, considering the influence of special mobility and intercultural experiences of life in their sense of belonging. We consider how identifications and mobility by two ethnographic researches about formative experiences of mbyà- Guaraní children of misiones province and Bolivian migrants living in Buenos Aires.By two life stories, we analyse how children participate in communities of practice linked with social reproduction in contexts of mobility, which imply generation’s distinctive experiences referred to school, productive activities and expressive dimensions of social life. Our research shows the children are active producers of identifications where origin territories idealized images are stressed by transformation’s process, evidence of inter-generation’s dynamicsof membership’s definitions.